Experimental work on micro laser-assisted diamond turning of silicon (111). (August 2015) - Mohammadi, Hossein; Ravindra, Deepak; Kode, Sai K.; Patten, John A.
Abstract: Single point diamond turning (SPDT) is coupled with the micro-laser assisted machining (μ-LAM) technique to machine silicon (111). The μ-LAM system is used to preferentially heat and thermally soften the work piece material in contact with a diamond cutting tool. Cutting fluid, odorless mineral spirits (OMS), is used to decrease tool wear and improve the surface quality. An IR continuous wave (CW) fiber laser, wavelength of 1070 nm and max power of 100 W with a minimum beam diameter of 10 μm, is used in this investigation. Various machining parameters such as laser power, cross feed rate and tool rake angle were experimented and the resultant surface finish was analyzed. Results show that an optical quality surface finish can be obtained using the μ-LAM technique.